LOKAL WISDOM PERNIKAHAN AGAMA KONGHUCU Di KELENTENG TJOE HWIE KIONG KOTA KEDIRI MENURUT UU PERNIKAHAN NO 1 TAHUN 1974 - Nur Kholis (Institut Agama Islam Ngawi, 2025)
Local wisdom in Confucian marriage is a manifestation of cultural values and spiritual teachings that govern sacred and meaningful matrimonial procedures. In Indonesia, marriage in Confucianism is not merely considered a bond between two individuals, but also a union of two families and a form of reverence towards ancestors and Tian (Heaven). The marriage process encompasses several stages, including the proposal report, family meeting, selection of an auspicious date based on the Confucian calendar, and the wedding ceremony itself, which is conducted through offering and prayer rituals at the temple. Within the context of national law, Law No. 1 of 1974 of the Republic of Indonesia concerning Marriage recognizes the validity of Confucian marriages, provided they adhere to appropriate customary provisions and procedures. This local wisdom emphasizes the importance of harmony, respect, and unity in building a strong family, aligning with state norms and regulations. Thus, Confucian marriage reflects a synergy between customary traditions, spirituality, and Indonesian legal regulations within a framework of sustainable local wisdom. The research method used is qualitative with an analytical descriptive approach. This approach allows researchers to thoroughly examine the values of local wisdom, the ritual practices of Confucian marriage, and their application within the national legal context. Applicable methods include: In-depth interviews: Collecting data from Confucian religious leaders, married couples, and marriage law experts to obtain direct perspectives on the integration of custom and law. Participatory observation: Directly observing Confucian wedding processions and practiced traditions to understand the preserved local values. Keywords: Local Wisdom, Confucian Marriage, Marriage Law.